2014
DOI: 10.1590/1984-70332014v14n3a25
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of Astrocaryum jauari (Mart.) palm in two Amazon river basins

Abstract: -Astrocaryum jauari is a non-domesticated palm that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
3
8
1
1
Order By: Relevance
“…Nevertheless, similar results for H E and H O were found for Chamaerops humilis, with a mean N A equal to 3.67 and H E and H O equal to 0.374 and 0.366, respectively (Giovino et al, 2014). It is worth mentioning that studies with other congeners of Astrocaryum (Oliveira et al, 2014;Ramos et al, 2012Ramos et al, , 2016) that used the same microsatellite set used here, excluded monomorphic loci from the estimation of genetic diversity; this automatically increased the estimates for these parameters [given the formula used to calculate heterozygosity (H = 2 ( 1)…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, similar results for H E and H O were found for Chamaerops humilis, with a mean N A equal to 3.67 and H E and H O equal to 0.374 and 0.366, respectively (Giovino et al, 2014). It is worth mentioning that studies with other congeners of Astrocaryum (Oliveira et al, 2014;Ramos et al, 2012Ramos et al, , 2016) that used the same microsatellite set used here, excluded monomorphic loci from the estimation of genetic diversity; this automatically increased the estimates for these parameters [given the formula used to calculate heterozygosity (H = 2 ( 1)…”
Section: Discussionsupporting
confidence: 72%
“…Other population genetic structure parameters, such as Wright's inbreeding coefficient and gene flow, have shown that, in general, genetic differentiation (F ST ) is low, indicating genetic variation higher within -rather than among -populations and a high gene flow among populations (Elshibli and Korpelainen, 2008;Martins-Corder et al, 2009;Shapcott et al, 2009;Namoff et al, 2011;Silva et al, 2011;Giovino et al, 2014;Nazareno and dos Reis, 2014;Oliveira et al, 2014;Moura et al, 2015). Recently, Ramos et al (2016) found a high level of genetic diversity, mostly within populations, for adults and seedlings in populations of A. aculeatum, and along with results for spatial genetic structure indicated short-distance seed dispersal and modest levels of pollen flow.…”
Section: Introductionmentioning
confidence: 99%
“…In palms, Oliveira et al (2014) found that the genetic structure of Astrocaryum jauari among different river sites within a river basin with high levels of gene flow within them, likely due to transport of fruits following the direction of the water currents. Mauritia swamps are a permanent or temporary shelter for many species of animals that maintain gene flow via seed dispersal (Mendieta-Aguilar, Pacheco, & Roldán, 2015), and fruits have the ability to undergo long-distance dispersal and float down rivers, traveling thousands of kilometers, connecting populations at large distances along the water (Moegenburg, 2002).…”
Section: Rivers Are Determinants Of Mauritia Flexuosa Population Stmentioning
confidence: 99%
“…In the present study, storage of leaflets in transport buffer for one week also proved to be a viable methodology for the preservation of plant tissue, since these leaflets retained the characteristics of fresh leaflets. Despite producing colour alteration in plant tissue, the silica gel method has been commonly used in the preservation of leaf samples of palm species such as "tucumanzeiro" (A. aculeatum), "açaizeiro" (E. oleracea), and "jauari" (A. jauari) (MILANI et al, 2009;OLIVEIRA et al, 2010;OLIVEIRA et al, 2014). The silica gel storage method has several advantages over other methods, owing to its simplicity, low cost, and the minimal space required for transport and storage in the laboratory.…”
Section: Resultsmentioning
confidence: 99%